Analysis of methanol maser flares in G107.298+5.63 and S255-NIRS3. (27th June 2020) - Gray, M D; Etoka, S; Pimpanuwat, B
ABSTRACT: A 3D maser model has been used to perform an inverse problem on the light curves from three high-amplitude maser flares, selected on the basis of contemporaneous infrared observations. Plots derived from the model recover the size of the maser cloud, and two parameters linked to saturation, from three observational properties of the light curve. Recovered sizes are consistent with independent interferometric measurements. Maser objects transition between weak and moderate saturation during a flare.